PowerPoint-Based Inquiry Tool Development for Active Learning and Process Skills - Sapulette, Cynthia. L.; Toisuta, Meike. E.; Pattiruhu, Claudia M; Labobar, Wilhelmus (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to: (1) produce a valid learning device with a PowerPoint-assisted inquiry approach to improve students' activeness and process skills; and (2) test the effectiveness of the device. This study is development research with a 4D model (Define, Design, Develop, Disseminate), but modified to 3D, only up to the development stage. The results of the study indicate that the developed device is valid and effective. The development achieved classical completeness with a score of 77 and an average of 96%. There is an influence of student activeness on learning completeness of 57.1%, and the influence of process skills of 70%. Simultaneously, activeness and process skills contribute 71% to learning completeness. Learning completeness in the trial class is higher than in the control class, and learning outcomes after learning are higher than before learning, indicating the effectiveness of the PowerPoint-assisted inquiry approach.